Skin-friction drag analysis from the forced convection modeling in simplified underwater swimming - Polidori, G.; Taiar, R.; Fohanno, S.; Mai, T. H.; Lodini, A. (Journal of Biomechanics, 2006)
This study deals with skin-friction drag analysis in underwater swimming. Although lower than profile drag, skin-friction drag remains significant and is the second and only other contribution to total drag in the case of underwater swimming. The question arises whether varying the thermal gradient between the underwater swimmer and the pool water may modify the surface shear stress distribution and the resulting skin-friction drag acting on a swimmer`s body. As far as the authors are aware, such a question has not previously been addressed. Therefore, the purpose of this study was to quantify the effect of this thermal gradient by using the integral formalism applied to the forced convection theory. From a simplified model in a range of pool temperatures (20-30 1C) it was demonstrated that, whatever the swimming speeds, a 5.3% reduction in the skin-friction drag would occur with increasing average boundary-layer temperature provided that the flow remained laminar. However, as the majority of the flow is actually turbulent, a turbulent flow analysis leads to the major conclusion that friction drag is a function of underwater speed, leading to a possible 1.5% reduction for fast swimming speeds above 1 m/s. Furthermore, simple correlations between the surface shear stress and resulting skin-friction drag are derived in terms of the boundary-layer temperature, which may be readily used in underwater swimming situations.